Theories and principles of urban and regional planning - Abdullahi, Hashim; Asmawi, M. Zainora (Pyla-mak Publishers Ltd, 2025)
The theory of urban and regional planning is a conceptual framework that guides the design, development, and management of cities and regions. It encompasses a set of ideas, principles, and methodologies used to understand, analyse and solve urban and regional challenges and problems. This theory draws from various disciplines, including geography, sociology, economics, architecture, environmental science, and political science, to create cohesive, co-existence and sustainable spaces. Thus, this book can be used in many inter-related fields in the built environment. This book addresses the pertinent topics related to urban and regional planning such as transportation planning, environmental planning and housing planning.